The competitiveness of Zimbabwe's exports to South Africa during the recovery period 2009 to 2011 - Nakunyada, Willie; Chikoko, Laurine (Sabinet, 2016)
This article analyses the competitiveness of Zimbabwe’s exports in the South African market under the multiple currency system from 2009 to 2011. Using real exchange rate analysis and the Revealed Symmetric Comparative Advantage index (RSCA), the article confirms that Zimbabwean products have lost competitiveness in South Africa, with comparative advantage only remaining in a narrow range of primary products. Based on the results, we recommend that deliberate policies be instituted to diversify and enhance the competitiveness of Zimbabwe’s exports.